Model Internet of thing untuk Pemantauan Pasien Isolasi Mandiri Menggunakan WEMOS D1R32 - Hallatu, Axl Denis B; Sulistyo, Wiwin (STMIK Banjarbaru, 2023)
Medical staff have the potential to contract the disease while treating Covid 19 patients in self-isolation status. This research aims to develop an Internet of Things model that can be used to monitor self-isolated patients, to reduce the risk of infection by medical personnel from certain diseases experienced by patients with Isolation status. The tool developed combines the function of WEMOS D1 R32 as a microcontroller equipped with ESP32 for sending data via the internet, the MLX90614 sensor for reading temperature and humidity, the hc-sr04 sensor is used so that the patient does not come into direct contact with the tool at a distance of less than 9 cm and the BUZZER is used as alarm if the patient's temperature is more than 38 Celsius, then to find out the patient's temperature, use the 16x2 12C LCD which has been installed on the device and also the blynk application which can be accessed via cellphone or web. WEMOS D1 R32 is connected to the MLX90614 sensor to find out the temperature of the patient who is in isolation independent. Obtained from the tests carried out each tool works well according to its function, and during testing the average tool delay from the sensor to blynk 1,870.Keywords: Wemos D1 R32; Blynk; Self isolation; Covid-19; mlx90614 AbstrakPetugas medis berpotensi tertular penyakit ketika sedang merawat pasien Covid 19 berstatus Isolasi Mandiri. Penelitian ini bertujuan mengembangkan model Internet of Thing yang dapat digunakan untuk memantau pasien isolasi mandiri, untuk mengurangi risiko tertularnya tenaga medis dari penyakit tertentu yang alami oleh pasien berstatu Isolasi. Alat yang dikembangkan menggabungkan fungsi WEMOS D1 R32 sebagai mikrokontroler yang dilengkapi dengan ESP32 untuk pengiriman data melalui internet, sensor MLX90614 untuk membaca suhu dan kelembaban,sensor hc-sr04 digunakan agar pasien tidak berkontak langsung dengan alat dengan jarak kurang dari 9 cm dan BUZZER digunakan sebagai alarm jika suhu pasien lebih dari 38 celcius ,kemudian untuk mengetahui suhu pasien digunakan LCD 16x2 12C yang telah dipasangkan pada alat dan juga aplikasi blynk yang dapat diakses melalui handphone maupun web.WEMOS D1 R32 dihubungkan dengan sensor MLX90614 untuk mengetahui suhu pasien yang sedang melakukan isolasi mandiri. Didapatkan dari tes yang dilakukan setiap alat bekerja dengan baik sesuai fungsinya, dan pada saat pengujian alat rata-rata delay dari sensor ke blynk 1.870.Kata Kunci: Wemos D1 R32; Blynk; Isolasi mandiri; Covid-19; Mlx90614